2018
DOI: 10.14196/mjiri.32.48
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nosocomial infections in Iran: A systematic review and meta-analysis

Abstract: Background: Nosocomial infections represent a serious public health concern worldwide, and, especially, in developing countries where, due to financial constraints, it is difficult to control infections. This study aimed to review and assess the prevalence of nosocomial infections in Iran. Methods: Different databases were searched between January 2000 and December 2017. To determine the pooled prevalence, the stochastic DerSimonian-Laird model was used, computing the effect size with its 95% confidence inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 35 publications
5
29
1
1
Order By: Relevance
“…In a meta-analysis of studies in Iran in 2018, the highest prevalence of HAIs was related to BSIs (9%), pneumonia (7.1%), SSIs (4.4%) and UTIs (3.1%), respectively [ 25 ]. The findings of our study about the most common HAIs are consistent with the results of Eshrati et al.’s 2018 study conducted on 7 018 393 cases of hospitalizations, and Zahraei et al.’s study in 2012 conducted on 1 879 356 patients admitted to hospitals in Iran; these two studies reported UTIs and VAP as the most prevalent types of infection, respectively [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of studies in Iran in 2018, the highest prevalence of HAIs was related to BSIs (9%), pneumonia (7.1%), SSIs (4.4%) and UTIs (3.1%), respectively [ 25 ]. The findings of our study about the most common HAIs are consistent with the results of Eshrati et al.’s 2018 study conducted on 7 018 393 cases of hospitalizations, and Zahraei et al.’s study in 2012 conducted on 1 879 356 patients admitted to hospitals in Iran; these two studies reported UTIs and VAP as the most prevalent types of infection, respectively [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, K. pneumoniae has become the most important causative agent of hospital infections, especially in Asian countries 1–3. Our surveillance data in China and reports from other parts of the world also showed that K. pneumoniae has become the most common clinically isolated bacterial pathogen and the most common bacterial pathogen that causes blood stream infection 4,5. Epidemic and endemic nosocomial infections caused by K. pneumoniae and related species are currently the leading cause of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 60%
“…3 Hip Prosthesis. 4 Such as Closed Reduction and Internal Fixation, amputation, correction of deformity, and Ilizarov.…”
Section: Resultsmentioning
confidence: 99%